2018
DOI: 10.1007/s00420-018-1300-0
|View full text |Cite
|
Sign up to set email alerts
|

Effort–reward imbalance in police work: associations with the cortisol awakening response

Abstract: ERI was inversely associated with the magnitude of awakening cortisol over time, indicating HPA axis dysregulation and potential future health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Elevated ERI was found to be linked to a significant decrease in peak, average, and total cortisol production among Buffalo, New York, police officers. 26 A very recent study found similar outcomes in a broader population sample. 27 Effort-reward imbalance has been linked to increased risk of depression (odds ratio [OR] 1.49; 1.23-1.80, P < .001) in a meta-analysis of 8 cohort studies involving almost 85,000 subjects.…”
Section: Scope and Impact Of Physician Burnoutmentioning
confidence: 78%
“…Elevated ERI was found to be linked to a significant decrease in peak, average, and total cortisol production among Buffalo, New York, police officers. 26 A very recent study found similar outcomes in a broader population sample. 27 Effort-reward imbalance has been linked to increased risk of depression (odds ratio [OR] 1.49; 1.23-1.80, P < .001) in a meta-analysis of 8 cohort studies involving almost 85,000 subjects.…”
Section: Scope and Impact Of Physician Burnoutmentioning
confidence: 78%
“…In the context of public health emergencies, working conditions and stress-related factors are among the most important determinants of mental health status among public health workers facing demanding work. The effort–reward imbalance model (ERI) is commonly used in research on work stress and working conditions in many professional populations, such as nurses [ 16 ], teachers [ 17 , 18 ], police officers [ 19 ] and doctors [ 20 ]. Additionally, the ERI model has been widely used to predict many stress-related physical and psychological disorders, such as hypertension [ 21 , 22 ], depression [ 16 , 23 ] and anxiety [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study [ 22 ] used self-reported questionnaires and pathognomonic clinical signs (trigger finger, Finkelstein’s test, Maudsley’s test, Hoffman–Tinel sign, and Phalen’s test) to evaluate upper extremity pain with different results; however, they also concluded that the questionnaire approach gives a good picture of the upper extremity locations with the possibility that the questionnaire can also underestimate severity. In addition, job-related stress in workplace has been accurately assessed by biological markers including saliva and urinary cortisol secretion, which are triggered by the hypothalamic–pituitary–adrenal (HPA) axis under stress and results in cortisol secretions intended to regain homeostasis [ 28 , 29 ]. Further research is needed to verify job-related stress levels by ERI compared to assessment by biological markers.…”
Section: Discussionmentioning
confidence: 99%